Multiscale modeling in biology - Schnell, S; Grima, R; Maini, P (2007)
Today, biologists and mathematicians work together not only to find structure in the vast quantities of data flowing from experiment but also to integrate this information into models that explain at multiple scales of time and space how life works. New tools are helping to see the regulatory and adaptive properties that characterize all biological phenomena. With the computing power to harness some of the data now available and with insights offered from old and new mathematics, modelers are making progress in many fronts. A specific area of development that is benefiting from such tools is the prevention of cancer.